2006
DOI: 10.1097/01.brs.0000216502.39386.70
|View full text |Cite
|
Sign up to set email alerts
|

Paragliding Accidents With Spinal Cord Injury: 10 Years?? Experience at a Single Institution

Abstract: Paragliding accidents with SCI show a characteristic injury pattern associated with a high recovery potential if the initial bony spinal canal occlusion is <70%. Half the patients will reintegrate in their former profession and place of employment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
1
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 28 publications
(29 reference statements)
2
11
1
1
Order By: Relevance
“…8,9 In contrast to these and to epidemiological data on SCI in Norway, paragliding injuries are more homogeneous, as serious neck and head trauma is rare, indicating that the spinal cord and spine are at high risk due to vertical highenergy force evoked toward the spine due to the paraglider's fixed body position. 1,3,10,11 Demographically, the paragliders with SCIs were similar to those in the general population of Norway, with clear male predominance. 10,11 Interestingly, most of the paragliders in our study were experienced, and the causes of accidents were unexpected circumstances and misjudgments in the landing process.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…8,9 In contrast to these and to epidemiological data on SCI in Norway, paragliding injuries are more homogeneous, as serious neck and head trauma is rare, indicating that the spinal cord and spine are at high risk due to vertical highenergy force evoked toward the spine due to the paraglider's fixed body position. 1,3,10,11 Demographically, the paragliders with SCIs were similar to those in the general population of Norway, with clear male predominance. 10,11 Interestingly, most of the paragliders in our study were experienced, and the causes of accidents were unexpected circumstances and misjudgments in the landing process.…”
Section: Discussionmentioning
confidence: 89%
“…Disabling loss of motility was found only in a few cases, as demonstrated also in other studies. 1,3 This may be explained by anatomical reasons, as spinal motoric areas and pathways are located farther from the influence of the spinal fracture.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[3,7] The mean age of the patients was also consistent with that reported in the literature. [1,2,8,9] Our review of the literature did not show any studies reporting a comparison of the characteristics of injuries between single and tandem paragliding accidents. Our results suggested that the rate of paragliding accidents is significantly higher in individual flights than in tandem flights (P<0.05).…”
Section: Discussionmentioning
confidence: 97%
“…Design and equipment have been refi ned until then. [1,2] This sport has gained popularity worldwide since its equipment is more affordable and easier to obtain than other kinds of aerial sports, and moreover, it does not require any logistical support such as an airport. It has been performed over Baba Mountain in the region of Fethiye in Turkey since the early 1990s ( Figure 1).…”
Section: Introductionmentioning
confidence: 99%